Building Fire Safety Audit at Faculty X, University of Indonesia, Year 2006 - Lestari, Fatma; Panindrus, RM. Yodan Amaral (Makara Journal of Technology, 2008)
Building Fire Safety Audit at Faculty X, University of Indonesia, Year 2006. Fire may cause loss of life, material and valuable assets. The objective of this study is to conduct audit for fire safety and emergency response in the building at Faculty X, University of Indonesia, Depok. The audit results on the building fire safety facilities including emergency response and preparedness are then compared to the Building Code Australia (BCA) and Indonesian regulation on the building fire safety (Kep.MenPU.No 10 and 11/KPTS/2000). The building selected are Building A, B, C, D, F and G. Building classification for A, B, D, F and G are classified as Class 5, while Building C is classified as Class 9b. Variable which are evaluated including emergency exit, building structure, fire alarm and detector, communication and fire warning system, evacuation procedure, portable fire extinguishers, hydrant, sprinkler, and emergency response preparedness. Results suggested that emergency exit is locked, and this is not comply to the regulation. Building structure has been complied to the regulation since it was made of concrete. Fire detector and alarm only provided in Building G, while other building is not available. There is no evacuation procedure available. Portable fire extinguisher has been available in all the building. Hydrant an sprinkler only available in building G. There is no emergency response preparedness in this faculty. In conclusion, the fire safety facilities in this faculty need to be improved.